Assessment of the Reasonability of the Division of Hadith Knowledge Into RIWĀYAH and DIRĀYAH - Helimy Aris; Amran Abdul Halim; Nazri Muslim (Human Resource Management Academic Research Society, 2024)
Vol 13, Issue 10